Posttraumatic Stress Disorder, Suicidal Ideation, and Suicidal Self-Directed Violence Among U.S. Military Personnel and Veterans: A Systematic Review of the Literature From 2010 to 2018 - Holliday, Ryan; Borges, Lauren M.; Stearns-Yoder, Kelly A.; Hoffberg, Adam S.; Brenner, Lisa A.; Monteith, Lindsey L. (Frontiers in Psychology, 2020)
Rates of suicide and posttraumatic stress disorder remain high among United States military personnel and veterans. Building upon prior work, we conducted a systematic review of research published from 2010-2018 regarding: (1) the prevalence of suicidal ideation, suicide attempt, and suicide among United States military personnel and veterans diagnosed with posttraumatic stress disorder; (2) whether posttraumatic stress disorder was associated with suicidal ideation, suicide attempt, and suicide among United States military personnel and veterans. 2,106 titles and abstracts were screened, with 48 articles included. Overall risk of bias was generally high for studies on suicidal ideation or suicide attempt and low for studies on suicide. Across studies, rates of suicidal ideation, suicide attempt, and suicide widely varied based on study methodology and assessment approaches. Findings regarding the association between posttraumatic stress disorder diagnosis with suicidal ideation and suicide were generally mixed, and some studies reported that posttraumatic stress disorder was associated with lower risk for suicide. In contrast, most studies reported significant associations between posttraumatic stress disorder and suicide attempt. These findings suggest complex associations between posttraumatic stress disorder and suicidal ideation, suicide attempt, and suicide, which are likely influenced by other factors (e.g., psychiatric comorbidity). In addition, most samples were comprised of veterans, rather than military personnel. Further research is warranted to elucidate associations between posttraumatic stress disorder and suicidal ideation, suicide attempt, and suicide, including identification of moderators and mediators of this relationship. Addressing this among United States military personnel, by gender, and in relation to different trauma types is also necessary.